Selection Signatures in Chinese Sorghum Reveals Its Unique Liquor-Making Properties - Zhang, Liyi; Ding, Yanqing; Xu, Jianxia; Gao, Xu; Cao, Ning; Li, Kuiying; Feng, Zhou; Cheng, Bing; Zhou, Lengbo; Ren, Mingjian; Lu, Xiaochun; Bao, Zhigui; et al. (Frontiers in Plant Science, 2022)
Chinese sorghum (S. bicolor) has been a historically critical ingredient for brewing famous distilled liquors ever since Yuan Dynasty (749 ~ 652 yr BP). Incomplete understanding of the population genetics and domestication history limits its broad applications, especially the lack of genetics knowledge underlying liquor-brewing properties makes it difficult to establish scientific standards for sorghum breeding. To unravel the domestic history of Chinese sorghum, we re-sequenced 244 Chinese sorghum lines selected from 16 provinces. We found that Chinese sorghums form three distinct genetic sub-structures, referred as the Northern, the Southern, and the Chishui groups, following an obviously geographic pattern. The Chinese sorghums were further characterized in liquor brewing traits and identified selection footprints associated with liquor brewing efficiency. An important selective sweep region identified includes several homologous genes involving in grain size, pericarp thickness, and architecture of inflorescence. Our result also demonstrated that pericarp strength rather than grain size determines the ability of the grains to resist repeated cooking during brewing process. New insight into the traits beneficial to the liquor-brewing process provides both a better understanding on Chinese sorghum domestication and a guidance on breeding sorghum as a multiple use crop in China.